IMAGE QUALITY ASSESSMENT FOR FAKE BIOMETRIC DETECTION USING SVM CLASSIFICATION - LUVIS, LINSHA; GNANA KING (Innovare Journal of Sciences, 2019)
Biometric security system plays very important role in everyone’s life as security. Biometric system is a security system which provides conditional ways after scanning for unique physical characteristics for authentication. But fake, synthetic or reconstructed sample is a main problem in biometric authentication. These biometric systems are highly flexible to different types of attacks such as some types of synthetically produced artifact (eg: fake fingerprints, photo print of iris image or face mask). Hence new and effective protection actions based on hardware and software have been developed to resist these attacks. Image quality assessment is one of the techniques used in image processing to decide whether the biometric input is real or synthetic .this paper deals with full reference and no reference measures used to estimate the quality value of an image.25 image quality features are takeout using mathematical expressions.